Ratio and race: On humanity and racism in Hegel - Sanguinetti, Federico (Revista Eletrônica Estudos Hegelianos, 2022)
In this paper, I will argue that Hegel’s thought is committed to racismand I will argue that Hegel’s racism conflicts with his conception of unversal humanity based on the possession of the capacity of reason. Moreover, I will highlight some theoretical issues stemming from an intepretive line of thought which suspects that Hegel’s universalistic humanism is inseparable or even derivable from his racism.